Condition assessment of bridges by dynamic measurements and finite element model updating - Xia, Pin Qi (2008)
In this thesis, a new and reliable method for accurate condition assessment of bridges is developed. Through the synthetic analysis, the concept of structural identification integrating the finite element (FE) analysis and experimental modal analysis was incorporated into the condition assessment of bridges.